Active and Passive Immunity against Borrelia burgdorferi Decorin Binding Protein A (DbpA) Protects against Infection - Hanson, Mark S. (American Society for Microbiology, 1998)
Borrelia burgdorferi, the spirochete that causes Lyme disease, binds decorin, a collagen-associated extracellular matrix proteoglycan found in the skin (the site of entry for the spirochete) and in many other tissues. Two borrelial adhesins that recognize this proteoglycan, decorin binding proteins A and B (DbpA and DbpB, respectively), have recently been identified. Infection of mice by low-dose B. burgdorferi challenge elicited antibodies against DbpA and DbpB that were sustained at high levels, suggesting that these antigens are expressed in vivo. Scanning immunoelectron microscopy showed that DbpA was surface accessible on intact borreliae. Passive administration of DbpA antiserum protected mice from infection following challenge with heterologous B. burgdorferi sensu stricto isolates, even when serum administration was delayed for up to 4 days after challenge. DbpA is the first antigen target identified that is capable of mediating immune resolution of early, localized B. burgdorferi infections. DbpA immunization also protected mice from B. burgdorferi challenge; DbpB immunization was much less effective. DbpA antiserum inhibited in vitro growth of many B. burgdorferi sensu lato isolates of diverse geographic, phylogenetic, and clinical origins. In combination, these findings support a role for DbpA in the immunoprophylaxis of Lyme disease and suggest that DbpA vaccines have the potential to eliminate early-stage B. burgdorferi infections.